Judges and wrongful convictions in Japan: a study of judicial culture - Ibusuki, Makoto (Law and culture in Japan, 2025)
Purpose: This chapter aims to explain the role judges play in producing wrongful convictions in Japan. Methodology/approach: Three types of evidence are presented: the writings of former judges; case studies of wrongful conviction; and data about the personnel evaluations that judges receive after initiating or vacating a retrial. Findings: Many judges in Japan fail to respect the principle that criminal suspects and defendants should be presumed innocent and that prosecutors bear the burden to prove guilt beyond a reasonable doubt. Case studies of wrongful conviction illustrate these tendencies, and data about judges’ careers suggest that the judiciary uses personnel evaluations to control judges by selectively punishing and rewarding them for how they handle cases. Because judges have the last word in Japanese criminal justice, they have an important responsibility in cases of wrongful conviction. Originality/value: This chapter makes three contributions to the literatures on wrongful conviction and the culture of criminal justice in Japan. First, it explains how judges help produce wrongful convictions and maintain them after they occur. Second, it shows that the behavior of judges is influenced by the organizational context and culture in which they work. Third, it discusses how wrongful convictions can be better prevented.